2021
DOI: 10.3389/fmicb.2021.686929
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and Molecular Phylogeny of Two New Species of Prostomatean Ciliates With Establishment of Foissnerophrys gen. n. (Alveolata, Ciliophora)

Abstract: Prostomatean ciliates play important roles in the flow of material and energy in aquatic microbial food webs, and thus have attracted wide attention for over a century. Their taxonomy and systematics are, however, still poorly understood because of their relatively few taxonomically informative morphological characters. In this study, two new prostomateans, Lagynus binucleatus sp. n. and Foissnerophrys alveolata gen. n., sp. n., collected from a freshwater pool and the intertidal zone of a sandy beach, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 56 publications
(76 reference statements)
2
13
0
Order By: Relevance
“…The molecular phylogeny of ciliates is mainly based on SSU rDNA sequence data, and this has helped to resolve a great number of systematic problems [6,9]. However, while some authors have detected higher interspecific variation using SSU rDNA [8,[10][11][12][13][14], others have obtained no or low sequence variability between certain congeners, or even between different genera, for example, in Pseudourostyla [15], Pseudouroleptus [16], Tetrahymena [17], Pseudokeronopsis [18], Euplotes [35], and Paramecium [65]. This indicates the low resolution of SSU rDNA as a species discriminator.…”
Section: Utility Of Ssu Rdna and Co1 As Biodiversity Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular phylogeny of ciliates is mainly based on SSU rDNA sequence data, and this has helped to resolve a great number of systematic problems [6,9]. However, while some authors have detected higher interspecific variation using SSU rDNA [8,[10][11][12][13][14], others have obtained no or low sequence variability between certain congeners, or even between different genera, for example, in Pseudourostyla [15], Pseudouroleptus [16], Tetrahymena [17], Pseudokeronopsis [18], Euplotes [35], and Paramecium [65]. This indicates the low resolution of SSU rDNA as a species discriminator.…”
Section: Utility Of Ssu Rdna and Co1 As Biodiversity Markersmentioning
confidence: 99%
“…To date, a variety of molecular methods (e.g., DNA-DNA hybridization, gene sequencing, and RAPD fingerprinting) have been used to assess genetic variation at different taxonomic levels [3,6,7]. Among these, comparisons of nuclear small-subunit ribosomal RNA gene (SSU rDNA) sequences are commonly applied [8][9][10][11][12][13][14]. However, recent studies have shown the limitations of SSU rDNA for discriminating closely related congeners [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, most prostomateans have only cursory original descriptions based exclusively on observations of live cells, with most of these occurring well before the molecular era (Carey 1992 ; Dragesco 1960 ; Kahl 1930 ). Only a handful of species have benefited from descriptions using modern techniques (Foissner 2021 ; Frantal et al 2022 ; Jiang et al 2021b , 2022 ; Sonntag et al 2022 ). There are also some ultrastructural studies of this group, which revealed details of several important characteristics such as the brosse and the extrusomes (Bardele 1999 ; Hiller 1991 , 1992 , 1993 ; Hiller and Bardele 1988 ; Lipscomb and Riordan 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lagynusids are typically elongated, the cell being divided into the “head”, annular neck-like region, and “trunk”, which is an unusual feature in prostomateans (Foissner et al 1995 ; Jiang et al 2021b ; Sola et al 1990 ). When established, Lagynusidae included only one monotypic genus Lagynus Quennerstedt, 1867, with Lagynus elegans (Engelmann, 1862) Quennerstedt, 1867 as the type species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation